Study on Room Temperature Ferromagnetism Behavior of Cr Doped CdSe Diluted Magnetic Nanostructures - Bansal, Amit (My University, 2011)
Diluted magnetic semiconductors (DMS), are semiconductors in which a magnetic impurity is intentionally introduced; a small fraction of the native atoms in the hosting non-magnetic semiconductor material is replaced by magnetic atoms. Incorporating of magnetic ions in semiconductors nanocrystallites, host materials modifying the optical, magnetic, and electronic properties. DMSs are ideal material for spin based electronics, i.e., Spintronics. The realization of functional spintronic devices requires materials with ferromagnetic ordering at operational temperatures compatible with existing semiconductor materials. Being a ferromagnetic semiconductor with favorable experimental properties, dilute magnetic semiconductors will promisingly suit this need. Pure and Cr-doped CdSe dilute magnetic semiconductors have been synthesized by solvothermal route. The particles were capped with 2-marcaptoethanol to achieve the stability. These samples are characterized by X-ray diffraction for structural and phase analysis. The optical properties were studied by photoluminescence; UV-visible absorption spectroscopy and Fourier transform infrared spectroscopy. The morphology of the synthesized nanoparticles was analyzed by Scanning electron microscope and transmission electron microscope. The magnetic measurements were done by vibrational sample magnetometer. The pure CdSe nanoparticles show diamagnetic behavior but Cr doped CdSe nanoparticle shows ferromagnetic behavior.
M.Sc. (Physics)
Keywords: Nanostructures; Dilutemanetic semiconductor